2002
DOI: 10.1139/g02-079
|View full text |Cite
|
Sign up to set email alerts
|

Geographic structure of genetic variation in the widespread woodland grassMilium effusumL. A comparison between two regions with contrasting history and geomorphology

Abstract: Allozyme variation in the forest grass Milium effusum L. was studied in 21-23 populations within each of two equally sized densely sampled areas in northern and southern Sweden. In addition, 25 populations from other parts of Eurasia were studied for comparison. The structure of variation was analysed with both diversity statistics and measures based on allelic richness at a standardised sample size. The species was found to be highly variable, but no clear geographic patterns in the distribution of alleles or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 36 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…The analysis of the partition of allelic variation is less common, although it has been often applied in plant studies (e.g. Petit et al1998;Comps et al 2001;Tyler 2002;Persson et al 2004;Stefenon et al 2008). Allelic richness is a measure of genetic variation somehow different from gene diversity.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the partition of allelic variation is less common, although it has been often applied in plant studies (e.g. Petit et al1998;Comps et al 2001;Tyler 2002;Persson et al 2004;Stefenon et al 2008). Allelic richness is a measure of genetic variation somehow different from gene diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, A ST considers the pairwise differences in absence/presence of alleles for each particular pair of subpopulations and, therefore, provides a specific assessment of the distances between subpopulations with respect to allelic composition. It has been argued that q ST largely depends on the distribution of rare alleles, notably whether they tend to be clustered in some subpopulations (high q ST ) or are distributed more evenly so that one subpopulation is representative of the whole population (low q ST ) (Comps et al 2001;Tyler 2002;Stefenon et al 2008). This is not very straightforward though.…”
Section: Discussionmentioning
confidence: 99%
“…The parameter q ST has been called A ST by several authors (e.g. Comps et al 2001;Tyler 2002;Persson et al 2004;Stefenon et al 2008). However, we will keep the original term to avoid further notation.…”
Section: Gene and Allelic Differentiation Between Subpopulationsmentioning
confidence: 99%
“…Conert et al . (), Tyler () and Valdés & Scholz also mention M. effusum subsp. alpicola Chrtek ( M .…”
mentioning
confidence: 99%
“…In the UK, for instance, this cultivar is sold by 55 suppliers across the country (Royal Horticultural Society ) and also in the US it is recommended for shady, moist habitats (Gunnel, Goodspeed & Anderson ). Allozyme studies have suggested the species to be highly variable with less genetic diversity in northern populations, but without clear geographic distribution of the diversity (Tyler ).…”
mentioning
confidence: 99%